Speed, Density, and Crash Relationship in Urban Arterial Roads - Kriswardhana, Willy; Sulistyono, Sonya; Widiarti, Wiwik Yunarni; Rahmawaty, Tiara Ayu (Fakultas Teknik Universitas Brawijaya, 2023)
Vehicle speed has an essential role in the occurrence of traffic accidents. Increasing the number of vehicles operating on the road will further increase the risk of traffic accidents because it is not balanced with discipline in driving. This study's purpose is to analyze the relationship between speed and traffic accidents that occurred in Gadjah Mada and Hayam Wuruk Road, Jember, through several variations of calculations. The independent variables used are average speed and 85th percentile speed and density, while the dependent variable used is the accident rate. The analysis used is a correlation test that determines the level of closeness of the relationship between the two variables and a regression test that helps estimate the relationship between the two variables through a regression equation model that will be selected based on conditions in the field. The results of this study indicate that lower speed is associated with a lower accident rate. Meanwhile, lower vehicle density leads to an increase in the accident rate. Speed management to improve traffic safety in Indonesia is needed. Direction for future research is presented.